Przejmowanie zbiorów artystycznych, archiwalnych i bibliotecznych śląskich krzyżowców z czerwoną gwiazdą podczas postępowania kasacyjnego w świetle "Akt Büschinga" - Bończuk-Dawidziuk, Urszula; Wojtyła, Arkadiusz (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny)
The paper consists of a source edition of documents pertaining the cassation of the St. Matthias convent of Knights of the Cross with the Red Star in Wrocław and its subordinate commanderies of St. Michael in Świdnica and of Saints Peter and Paul in Ziębice. All three were appropriated by the Prussian state based on the secularisation edict of 1810. The edition was complemented by a historical commentary introducing the readers to the character of the sources and inincluding a concise description of their contents. The presented files provide information primarily on the cassation proceedings.
Keywords: Wrocłąw; Świdnica (Polska; woj. dolnośląskie); Ziębice